2006
DOI: 10.1111/j.1440-1746.2006.04355.x
|View full text |Cite
|
Sign up to set email alerts
|

Erosive esophagitis in the Philippines: A comparison between two time periods

Abstract: The prevalence of EE was higher in 2000-2003 than in 1994-1997, although the complications associated with the disease diminished. The prevalence of concomitant Barrett's esophagus remained stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…In the western countries, hospitalization and mortality rates for peptic ulcer and gastric cancer had dropped substantially from 1970 and 1995, while hospitalisation rates for GERD and esophageal adenocarcinoma rose significantly [15]. In Asia, similar rising trend of symptomatic GERD, endoscopic esophagitis and even esophageal adenocarcinoma has been observed in many retrospective endoscopy-based studies, and these changes in prevalence were coincident with a decline in prevalence of H. pylori infection, peptic ulcer and gastric cancers [16][17][18][19][20].…”
Section: Opposing Secular Trends Of H Pylori Related Diseases and Gerdmentioning
confidence: 81%
“…In the western countries, hospitalization and mortality rates for peptic ulcer and gastric cancer had dropped substantially from 1970 and 1995, while hospitalisation rates for GERD and esophageal adenocarcinoma rose significantly [15]. In Asia, similar rising trend of symptomatic GERD, endoscopic esophagitis and even esophageal adenocarcinoma has been observed in many retrospective endoscopy-based studies, and these changes in prevalence were coincident with a decline in prevalence of H. pylori infection, peptic ulcer and gastric cancers [16][17][18][19][20].…”
Section: Opposing Secular Trends Of H Pylori Related Diseases and Gerdmentioning
confidence: 81%
“…19,20 The prevalence rates reported form Turkey are markedly lower than those determined in western countries. In their prospective study, Odemiş et al 21 have reported a BE prevalence of 1.2% in Turkish patients undergoing endoscopy for any reason.…”
Section: Discussionmentioning
confidence: 96%
“…Erosive esophagitis was observed in 36% of them, the majority of which was of grade LA-A or LA-B. Longitudinal studies conducted in Asia show an increase in the prevalence of GERD symptoms and reflux esophagitis (9-11). The ratio of erosive reflux disease (ERD) to nonerosive reflux disease (NERD) in Asia is believed to be lower than in the West (12).…”
Section: Discussionmentioning
confidence: 99%